Model Validation of Radiocaesium Transfer from Soil to Leafy Vegetables - P. Sukmabuana; P.I. Tjahaja (Atom Indonesia, 2012)
The accumulation of radionuclide in plant tissues can be estimated using a mathematical model, however the applicability of the model into field experiment still needs to be evaluated. A model validation has been conducted for radiocaesium transfer from soil to two leafy vegetables generally consumed by Indonesian people, i.e. spinach and morning glory in order to validate the transfer model toward field experimental data. The vegetable plants were grown on the soil contaminated with 134CsNO3 of 19 MBq for about 70 days. As the control, vegetables plant were also grown on soil without 134CsNO3 contamination. Every 5 days, both of contaminated and un contaminated plants were sampled for 3 persons respectively. The soil media was also tested. The samples were dried by infra red lamp and then the radioactivity was counted using gamma spectrometer. Data of 134Cs radioactivity on soil and plants were substituted into mathematical equation to obtain the coeficient of transfer rate (k12). The values of k12 were then used for calculating the 134Cs radioactivity in the vegetable plants. The 134Cs radioactivity in plants obtained from mathematical model analysis was compared with the radioactivity data obtained from the experiment. Correlation of 134Cs radioactivity in vegetables plant obtained from the experiment with those obtained from model analysis was expressed as correlation coefficient, and it was obtained to be 0.90 and 0.71 for spinach and morning glory plants respectively. The values of 134Cs in plants obtained from the model analysis can be corrected using standard deviation values, namely 48.65 and 20 for spinach at 0<t<55 days and at 0<t<78 days, respectively. Whereas for morning glory the standard deviation value was 0.36. Although there are differences between 134Cs radioactivity in vegetable plants obtained from model analysis and experiment data, the model of 134Cs transfer from soil to plant can be used for analysing 134Cs radioactivity on leafy vegetable plants grown on radiocesium contaminated soil. Received:  31 March 2010;  Revised: 23 April  2012;  Accepted:  27 April 2012